Phylogenetic and morphological resolution of the Helobdella stagnalis species-complex ( Annelida: Clitellata: Hirudinea) (vol 4403, pg 61, 2018) - Saglam, Naim; Kutschera, Ulrich; Saunders, Ralph; Saidel, William M.; Balombini, Katherine L. W.; Shain, Daniel H. (Magnolia Press, 2019)
[Abstract Not Available]